Comparison of the Effects of Attachment Training for Mothers on the Behavioral Responses of Premature Infants: A Randomized Clinical Trial - Mitra Edraki; Sahra Zendehzaban; , Nooshin Beheshtipour; Fariba Hemmati; Sezaneh Haghpanah (Mashhad University of Medical Sciences, 2015)
Background: Premature infants are among high-risk groups in community who need to be hospitalized at intensive care units for survival and receiving basic or special care. Hospitalization at neonatal intensive care units (NICUs) unsettles the family and leads to the separation of parents from their infants. This study aimed to determine the effects of maternal attachment behaviors on the behavioral responses of premature infants, hospitalized at NICUs. Methods: In this randomized clinical trial, 64 premature infants, who were hospitalized at NICUs and were eligible for the study, were randomly allocated to study and control groups. Attachment behaviors including touching, massage and kangaroo care were applied for the study group, while the conventional attachment method was adopted for the control group. Behavioral responses were evaluated two hours before and two hours after training attachment behaviors. Data were analyzed, using Chi-square and student's t-test. Results: The mean difference in the duration of deep sleep and consciousness was more significant in the study group, compared to the control group. Furthermore, the duration of drowsiness was significantly less in the study group, compared to the control group. Conclusion: The implementation of attachment training at NICUs decreased the time of drowsiness and improved behavioral responses, deep sleep time and consciousness.